2009
DOI: 10.1186/1743-422x-6-166
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of virion associated host proteins in vesicular stomatitis virus using a proteomics approach

Abstract: Background: Vesicular stomatitis virus (VSV) is the prototypic rhabdovirus and the best studied member of the order Mononegavirales. There is now compelling evidence that enveloped virions released from infected cells carry numerous host (cellular) proteins some of which may play an important role in viral replication. Although several cellular proteins have been previously shown to be incorporated into VSV virions, no systematic study has been done to reveal the host protein composition for virions of VSV or … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
45
0
2

Year Published

2011
2011
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 44 publications
(48 citation statements)
references
References 65 publications
1
45
0
2
Order By: Relevance
“…Virus Production-Vesicular stomatitis virus (VSV) was prepared as described previously (35). In brief, ARPE-19 cells were inoculated with VSV, and virus containing media were collected at 24 h postinfection.…”
Section: Generation Of Soluble Tam Receptor Construct and Pngasefmentioning
confidence: 99%
“…Virus Production-Vesicular stomatitis virus (VSV) was prepared as described previously (35). In brief, ARPE-19 cells were inoculated with VSV, and virus containing media were collected at 24 h postinfection.…”
Section: Generation Of Soluble Tam Receptor Construct and Pngasefmentioning
confidence: 99%
“…Importantly, phylogenetic analysis using the N gene sequence demonstrated that CTNCEC25 was more closely related to China indigenous RABV strains than other vaccine strains used in China using the complete genome sequence, the mature G protein amino acid sequence and the N gene sequence. As it has been shown that variations existed in virus-neutralizing antibody titer values when heterologous virus strains other than homologous virus strains were used as the challenge virus [18,19], it is therefore reasonable to assume that the best vaccine strain should be the one most closely related to the circulating strains within a target area. Further studies are undertaken to unravel the potential application of CTNCEC25 in rabies prevention and control in China.…”
Section: Resultsmentioning
confidence: 99%
“…In addition to IAV, AnxA1 is found associated with several other viruses [114][115][116][117][118][119][120][121][122]. Interestingly, no indications so far suggest that the viruses rely on its immune-modulating capacity to facilitate virus entry, although the AnxA1 receptor FPR2 is involved in IAV replication [123].…”
Section: Annexins and The Host/pathogen Interfacementioning
confidence: 99%